Teacher Performance at SMPN 1 Rebang Tangkas: The Effects of Work Environment and HR Competencies - Handayani, Fitri; Andayani, Sri (Universitas Sang Bumi Ruwa Jurai, 2024)
Many organizations experience changes in an increasingly competitive environment, where employee dissatisfaction can occur more frequently. If dissatisfaction arises, the stability and success of the organization will be hindered. The phenomenon occurring at SMPN 1 Rebang Tangkas, Way Kanan Regency, regarding the work environment, cannot yet be considered conducive. Although a harmonious relationship among teachers has been established from a non-physical aspect, this is not supported by a physical work environment that is damaged and not functioning well. Based on this, the purpose of this research is to determine: 1) The effect of the work environment on employee performance; 2) The effect of human resource competencies on employee performance; and 3) The combined effect of the work environment and human resource competencies on employee performance at SMPN 1 Rebang Tangkas, Way Kanan Regency. This study uses a descriptive quantitative research method with simple and multiple regression analysis. The sampling technique used in this study is total sampling, resulting in a sample of 22 respondents. Based on the data analysis results, it was found that: 1) There is an effect of the work environment (X1) on employee performance (Y) at SMPN 1 Rebang Tangkas, Way Kanan Regency; 2) There is an effect of competencies on employee performance at SMPN 1 Rebang Tangkas, Way Kanan Regency; and 3) There is a combined effect of the work environment and competencies on employee performance at SMPN 1 Rebang Tangkas, Way Kanan Regency.